Photomodulation Approaches to Overcome Antimicrobial Resistance - Sofia N. Sarabando; Andreia Palmeira; Maria Emília Sousa; Maria Amparo F. Faustino; Carlos J. P. Monteiro (MDPI AG, 2023)
Photopharmacology is an approach that aims to be an alternative to classical chemotherapy. Herein, the different classes of photoswitches and photocleavage compounds and their biological applications are described. Proteolysis targeting chimeras (PROTACs) containing azobenzene moieties (PHOTACs) and photocleavable protecting groups (photocaged PROTACs) are also mentioned. Furthermore, porphyrins are referenced as successful photoactive compounds in a clinical context, such as in the photodynamic therapy of tumours as well as preventing antimicrobial resistance, namely in bacteria. Porphyrins combining photoswitches and photocleavage systems are highlighted, taking advantage of both photopharmacology and photodynamic action. Finally, porphyrins with antibacterial activity are described, taking advantage of the synergistic effect of photodynamic treatment and antibiotic therapy to overcome bacterial resistance.